REFORMULASI TINDAK PIDANA POLITIK UANG KAJIAN TERHADAP PASAL 523 UNDANG-UNDANG NOMOR 7 TAHUN 2017 TENTANG PEMILU - Aryanto, Fickry; Firdaus, Emilda; R, Mukhlis (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2020)
In the context of upholding democracy, efforts to protect the integrity of elections are very important. When looking at the latest standards (compliance and enforcement of election laws), it is important to ensure fair elections. Adamya several cases of money politics in the election practice in damaging the administration of the election itself. Thus, money politics is categorized as a serious problem in the election. That is because money politics has a bad impact on elections and strengthening democracy.This type of research can be classified in normative legal research, namely legal research conducted by examining library materials. This study examines the subject matter in accordance with the scope and identification of problems through a statute approach carried out by examining the laws and regulations relating to the legal issues under study. In this study the authors conducted a study of legal principles by utilizing descriptive methods. The data collection technique used is the method of researching library data that is utilizing the library as a means of collecting data, by studying books as reference material related to the problem to be studied.The conclusion that can be obtained from the results of the study is the regulation of criminal law against money politics based on Article 523 of Law Number 7 of 2017 Regarding Elections, which is still unclear and unequivocal. Highlighting the weaknesses of regulations regarding money politics in the 2019 elections. Law Number 7 of 2017 concerning Elections has not been able to punish all people who have been proven to receive or give money for political purposes. People who can be punished are those who do money politics and are listed in the success team. Cases of money politics committed in the conduct of elections but cannot yet be sanctioned due to limitations of the law in regulating money politics crimes. An ideal arrangement for money politics based on positive Indonesian law is urgently needed in order to achieve free and fair elections. Therefore mistakes or weaknesses at the policy / legislation / formulation stage are strategic errors that can become obstacles to law enforcement efforts. Renewal of criminal law in the context of overcoming crime becomes very important, because mistakes in substance or formulations are very strategic mistakes for mistakes in the next stages.Keywords: Reformulation, Crime, Money Politics, Elections